PENGARUH MOTIVASI, PENGETAHUAN PERPAJAKAN DAN KESADARAN PAJAK TERHADAP KEPATUHAN PAJAK PADA KPP PRATAMA DEPOK SAWANGAN - Wadi, Indra; Akbar, Mhd Ali (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
Tax compliance is a critical aspect of a well-functioning tax system, and understanding the factors that influence taxpayers' compliance behavior is essential for effective tax administration. This research focuses on investigating the impact of motivation, tax knowledge, and tax awareness on tax compliance among taxpayers served by the Sawangan Primary Tax Office (KPP Pratama Depok Sawangan). The main objective of this study is to analyze and assess the relationships between motivation, tax knowledge, tax awareness, and tax compliance. By gaining insights into these relationships, the research aims to contribute to the enhancement of tax compliance strategies and policies in the jurisdiction of the Sawangan Primary Tax Office. This research employs a quantitative approach, utilizing a survey method to collect data from a sample of taxpayers registered with the KPP Pratama Depok Sawangan. A structured questionnaire is designed to measure variables such as motivation, tax knowledge, tax awareness, and tax compliance. The collected data will be analyzed using statistical tools, including regression analysis, to identify the significance and strength of the relationships among the variables. The population of this study is individual taxpayers who are registered at KPP Pratama Depok Sawangan. The findings of this study suggest that there is a significant impact of motivation, tax knowledge, and tax awareness on tax compliance at the Sawangan Primary Tax Office (KPP Pratama Depok Sawangan). In other words, the level of motivation, understanding of taxation, and awareness of tax obligations among taxpayers in this jurisdiction play crucial roles in influencing their compliance with tax regulations.